Enhanced Q-switching performance of magnetite nanoparticle via compositional engineering with Ti3C2 MXene in the near infrared region. (10th August 2021) - Hu, Yutao; Chu, Hongwei; Li, Daozhi; Li, Ying; Zhao, Shengzhi; Dong, Li; Li, Dechun
Graphical abstract: Highlights: FONPs were modified via the compositional engineering with the Ti3C2 MXene for the first time. The first-principle simulation was applied to investigate the band structure and work function. The OA Z-scan was used to obtain the nonlinear optical properties of FONPs@Ti3C2 MXene hybrid. The first demonstration with FONPs@Ti3C2 MXene hybrid saturable absorber was realized in NIR region. The minimum pulse duration of 99 ns was achieved with a stable Q-switching operation. Abstract: In this work, we reported a new strategy to improve the nonlinear saturable absorption performance of magnetite (Fe3 O4 ) nanoparticles (FONPs) via the compositional engineering with the Ti3 C2 MXene in the near-infrared (NIR) region. Based on the DFT simulation, the band structures and work function were significantly modified by the Ti3 C2 MXene doping. By using the open-aperture Z-scan technology, the nonlinear optical features of the FONPs@Ti3 C2 nanocomposite were significantly improved, showing the great potential as the saturable absorber in the pulsed laser. With the nanocomposite as the saturable absorber, the passively Q-switched Nd:GdVO4 lasers emitted much shorter pulse durations when compared with the pristine FONP saturable absorber. These findings indicated that FONPs@Ti3 C2 heterostructure was a promising saturable absorber for the short pulse generation in the NIR region.